2014
DOI: 10.1007/s10802-014-9897-2
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Level Risk Factors for Suicidal Ideation Among at-Risk Adolescent Females: The Role of Hypothalamic-Pituitary-Adrenal Axis Responses to Stress

Abstract: Adopting a multi-level approach, this study examined risk factors for adolescent suicidal ideation, with specific attention to (a) hypothalamic-pituitary-adrenal (HPA) axis stress responses and (b) the interplay between HPA-axis and other risk factors from multiple domains (i.e., psychological, interpersonal and biological). Participants were 138 adolescent females (Mage=14.13 years, SD=1.40) at risk for suicidal behaviors. At baseline, lifetime suicidal ideation and a number of risk factors were assessed (i.e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
67
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 60 publications
8
67
1
Order By: Relevance
“…This finding is contrary to Giletta et al (2015) who found that heightened cortisol reactivity to stress was the strongest predictor of suicide ideation at three-month follow-up in at-risk adolescent females. This study also found a subsample of adolescents who exhibited a blunted response to stress and high levels of suicide ideation 3-months later (though, this effect was only a trend).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This finding is contrary to Giletta et al (2015) who found that heightened cortisol reactivity to stress was the strongest predictor of suicide ideation at three-month follow-up in at-risk adolescent females. This study also found a subsample of adolescents who exhibited a blunted response to stress and high levels of suicide ideation 3-months later (though, this effect was only a trend).…”
Section: Discussioncontrasting
confidence: 99%
“…In the context of suicide research, the majority of previous work has focused on assessing HPA axis functioning through pharmacological manipulation of the stress system (e.g., see Coryell and Schlesser, 2001;Coryell et al, 2006;Mann and Currier, 2007;Pompili et al, 2010). However, recently researchers have turned their attention to investigating other aspects of the cortisol response, such as cortisol reactivity to laboratory stressors (e.g., Giletta et al, 2015;McGirr et al, 2010). McGirr and colleagues (2010) explored the extent to which dysregulation of the HPA axis to a laboratory stressor was a heritable risk factor for suicidal behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example an enhanced cortisol response to the TSST has been shown to predict depressive symptoms in young adults (Morris et al, 2012) and suicidal ideation in female adolescents with a history of mental health concerns (Giletta et al, 2014). The results are also consistent with evidence showing greater cortisol reactivity to the TSST in older adults subjected to separation from both parents during childhood (Pesonen et al, 2010) and in young adults exposed to severe pre-natal stress (Entringer et al, 2009).…”
Section: Insert Table 2 Heresupporting
confidence: 66%
“…Once released, cortisol has several important functions such as increasing access to energy stores, increasing protein and fat mobilisation, as well as regulating the magnitude and duration of inflammatory responses (Sapolsky et al, 2000). Cortisol has also been found to be associated with impairments in cognitive control, decision-making and emotional processing linked to suicidal behavior (Giletta et al, 2015;Turecki et al, 2012). As such, cortisol is the primary effector hormone of the HPA axis stress response system and has received extensive empirical investigation.…”
Section: Introductionmentioning
confidence: 99%